Copernicium: A Relativistic Noble Liquid - Mewes, Jan‐Michael; Smits, Odile R.; Kresse, Georg; Schwerdtfeger, Peter (Angewandte Chemie, 2019)
The chemical nature and aggregate state of superheavy copernicium (Cn) have been subject of speculation for many years. While strong relativistic effects render Cn chemically inert, which led Pitzer to suggest a noble‐gas‐like behavior in 1975, Eichler and co‐workers in 2008 reported substantial interactions with a gold surface in atom‐at‐a‐time experiments, suggesting a metallic character and a solid aggregate state. Herein, we explore the physicochemical properties of Cn by means of first‐principles free‐energy calculations, which confirm Pitzer's original hypothesis: With predicted melting and boiling points of 283±11 K and 340±10 K, Cn is indeed a volatile liquid and exhibits a density very similar to that of mercury. However, in stark contrast to mercury and the lighter Group 12 metals, we find bulk Cn to be bound by dispersion and to exhibit a large band gap of 6.4 eV, which is consistent with a noble‐gas‐like character. This non‐group‐conforming behavior is eventually traced back to strong scalar‐relativistic effects, and in the non‐relativistic limit, Cn appears as a common Group 12 metal. Die physikochemischen Eigenschaften von Copernicium (Cn) wurden mit Ab‐initio‐Freie‐Energie‐Rechnungen untersucht. Mit berechneten Schmelz‐ und Siedepunkten von 283±11 K und 340±10 K ist Cn eine flüchtige Flüssigkeit. Obwohl diese metallischem Quecksilber von der Dichte her sehr ähnlich ist, dominieren in flüssigem Cn Dispersionswechselwirkungen, was zusammen mit einer berechneten Bandlücke von 6.4 eV auf edelgasähnliche Eigenschaften hindeutet.